Operation K-9 Brothers - Owens, Sandra (Operation K-9 Brothers, 2021)
"Navy SEAL Jack Daniels (save the jokes, he's heard them all) and his trusty Belgian Malinois sidekick Dakota are back home in Asheville, North Carolina, after a bomb left them scarred. Unable to accept that he'll never be able to return to his team, Jack is looking for a miracle. What he isn't looking for is a permanent relationship, though he's open to a no-strings distraction at the magic hands of gorgeous local potter Nichole Masters"--Back cover.